Treinamento ambiental:revisão de literatura e sugestões de pesquisa - Moraes, Silvana de Souza [UNESP]; Battistelle, Rosane Aparecida Gomes [UNESP] (A Fundacao para o Desenvolvimento de Bauru (FunDeB), 2015)
This article aims to list the studies on environmental training published in the Scopus and Web of Science databases, to emphasize the publications most relevant according to the number of citations in other research, list the most prominent authors regarding the topic, the contexts studied and the researcher’s countries of origin. The concepts of environmental management and environmental training were reviewed. The systematic literature review is presented as the methodology, which has as its results the identification of the most influential papers studied in the area, the countries of origin of researchers and the relation between context and origin of the researcher, concluding that Brazil stands out in the study of the theme. That there is a small number of researchers studying different contexts in their country of origin and that partnership between researchers from different countries are required for studies in the area. The study presents as a limitation the still restricted access to some journals presenting articles on the topic, making it impossible to analyze them. It contributes with researchers and those responsible for human resource managers in organizations because it shows the most relevant studies of the area in a compiled form.

Este artigo tem como objetivo elencar os trabalhos sobre treinamento ambiental publicados nas bases de dados Scopus e Web of Science, destacar as publicações de maior relevância de acordo com o número de citações em outras pesquisas, elencar os autores de maior destaque em relação ao tema, os contextos estudados e os países de origem dos pesquisadores. Foram revisadosos conceitos de gestão ambiental e treinamento ambiental. Apresenta como metodologia a revisão sistemática de literatura e tem como resultados a identificação de artigos de grande influência na área, os contextos mais estudados, os países de origem dos pesquisadores e a relação entre contexto estudado e origem do pesquisador,concluindo-se que o Brasil se destaca no estudo do tema, que é pequeno o númerode pesquisadores que estudam contextos diferentes do seu país de origem e que parcerias entre pesquisadores de diferentes países são necessárias para estudos na área. O estudo apresenta como limitação o acesso ainda restrito a alguns jornais que apresentam artigos sobre o tema, impossibilitando a análise dosmesmos. Contribui com pesquisadores e responsáveis pela gestão de recursos humanos das organizações, visto que apresenta os estudos mais relevantes na área de forma compilada.
Environmental training: literature review and suggestions for research
Keywords: Environmental management; Environmental training; Literature review; Gestão ambiental; Treinamento ambiental; Revisão de literatura